The Growing American Health Penalty: International Trends in the Employment of Older Workers with Poor Health - Ben Baumberg Geiger; René Böheim; Thomas Leoni (Institute of Labor Economics (IZA), 2018)
Many countries have reduced the generosity of disability benefits while making them more activating – yet few studies have examined how employment rates have subsequently changed. We present estimates of how the employment rates of older workers with poor health in 13 high-income countries changed between 2004-7 and 2012-15 using HRS/SHARE/ELSA data. We find that those in poor health in the USA have experienced a unique deterioration: they have not only seen a widening gap to the employment rates of those with good health, but their employment rates fell per se. We find only for Sweden (and possibly England) signs that the health employment gap shrank. We then examine possible explanations for the development in the USA: we find no evidence it links to labour market trends, but possible links to the USA's lack of disability benefit reform – which should be considered alongside the wider challenges of our findings for policymakers.
Keywords: J14; J18; H55; 330; disability benefits; employment of older workers; health employment gap